2017
DOI: 10.20870/oeno-one.2017.51.2.1829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil type on vineyard performance and berry composition in the Río de la Plata Coast (Uruguay)

Abstract: <p style="text-align: justify;"><strong>Aims:</strong> Vineyards in Uruguay are concentrated over soils formed from Quaternary sediments; however, in recent years vineyard surface over soils formed from metamorphic rocks has increased. In this context, this study assessed the relationships between soil physical properties and grapevine vegetative development, yield and berry composition, in order to understand how vine response is affected and characterize the viticultural production potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
0
13
1
2
Order By: Relevance
“…Soil characteristics and topography, together with climate, are the components of terroir that most influence grapevine growth and fruit quality . Different studies have demonstrated the relationship between some soil properties and grape and wine characteristics . On one hand, soil particles and pore distribution govern, both directly and indirectly, many physical, chemical, and biological aspects of the soil, and affect water and nutrient movement, soil hydraulic properties, and drainage .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Soil characteristics and topography, together with climate, are the components of terroir that most influence grapevine growth and fruit quality . Different studies have demonstrated the relationship between some soil properties and grape and wine characteristics . On one hand, soil particles and pore distribution govern, both directly and indirectly, many physical, chemical, and biological aspects of the soil, and affect water and nutrient movement, soil hydraulic properties, and drainage .…”
Section: Introductionmentioning
confidence: 99%
“…indicate impacts of texture on fruit composition and also on vine vigor and vine earliness. Echeverría et al . indicated that the available water in the root zone is one of the factors that affect plant growth, yield, bunch rot, and berry composition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations